Membangun Budaya Madrasah - Barnawi, Barnawi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Madrasah culture is a set ofvalue systems believed to be formulated in a madrasah vision and mission as well as actualized in the lives of all citizens of the madrasah. If any madrasah has culture of each course will enrich and comparative advantage madrasas, however, must be aligned with the value system of universal values that can be accepted by the whole society. Madrasah culture and value system espoused Islamic community is a chain that led to the out come of quality education, in the sense of having a strong personality and be a civilized human being. In the perspektif of philosophy, a cultured man is a man who is able to teach itself towards the better. Seeing the importance of madrasah culture and its strategic position in shaping the character of the building culture of madrasah graduates is a necessity, it’s then that the interests of this writing. Keywords : culture, madrasas, value.